Prevalence of Hearing Loss in Children of Parents with Consanguineous Marriages - Sehar Batool, Muhammad Azzam Khan, Amna Asghar, Bushra Naseer, Shahid Waheed, Bilal Hussain, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: According to the World Health Organization, 6.1% of the world's population has hearing impairment, making it one of the most common disabilities. Congenital, prenatal, genetic, and environmental factors are among the many causes of hearing impairment. Congenital hearing loss is thought to be mostly caused by consanguinity. Numerous studies, both in the Middle East, where the practice is very common, and in Europe, where it is taboo, show a strong connection between congenital hearing loss and consanguinity. There is virtually little research on hearing loss brought on by consanguinity in the literature. Objective: The find the prevalence of hearing loss in children of parents with consanguineous marriages. Material & Methods: This an observational cross-sectional study. The study had a sample size of 377 subjects. The data was collected from Alam Audiology Clinic and Sir Ganga Ram Hospital for 6 months from January to June, 2022. The data was collected from parents who reported a consanguineous marriage, and the children were taken between the ages of 0.5 years to 5 years, children were test using various audiological intervention, i.e., Pure Tone. Audiometry, Otoacoustic emissions, Auditory Brain-stem Response. The children who were syndromic or had other associated psychological issues were excluded. A Performa was generated inquiring about demographics, nature of consanguinity, other disabilities type of hearing impairment and other risk factors, this was filled out by the parents or the researcher in consultation of the parents. All the parents were informed of the study and their consent was taken. The study data was analyzed using SPSS 21 and frequencies were found out, tables and charts were systematically drawn and their conclusions were drawn. The study followed all ethical parameters. Results: The results showed that out of the 377 participants, 186 were male and 191 were females, children of the age group 2-5 years were the most extensive numbering 323 participants (85.7%). An overwhelming number of children brought for assessment were with congenital hearing loss 286 (75.9%). Very few people reported hearing impairment in their family history. The nature of the cousin marriage shows that most of the participants 78.2% reported that they are first cousins. Most of the children 69% had moderate to severe hearing loss. Practical Implication: The study will show us the impact of consanguineous marriages have on the hearing capacity of their children. The study will highlight consanguineous marriages as a factor in hearing impairment. Keywords: Hearing loss, consanguinity, hearing impairment, hearing impairment.